Development of Adsorbent Hollow Fibres for Environmental Applications - Chin-Chih Tai; Yun-Hsin Wang (Adsorption Science & Technology)
In this paper, a new generic synthesis route for the single-step production of adsorbent hollow fibres, based on polymer dry/wet spinning followed by a phase inversion process, is presented. This main advantage of this preparation technique is that it avoids impregnation of precursors or the use of chemicals for zeolite deposition, while dramatically reducing production times and costs. Primary factors (polymer, solvent and temperature) affecting the structure and adsorption performance of adsorbent hollow fibres are studied. The adsorptive properties of HiSiv 3000 hollow fibres and their commercial particulate counterpart have been obtained in a laboratory-scale flow system using n-butane as the adsorbate. The fibres prepared from solvents such as N, N-dimethylformamide, N, N-dimethylacetamide and 1-methyl-2-pyrrolidone (NMP) and from three types of polymers, namely, polysulfone, polyethersulfone (PESF) and polyvinylidenefluoride, are compared. The adsorbent hollow fibre prepared from NMP/PESF gave the sharpest breakthrough curve and the longest breakthrough time compared with others including commercial adsorbent pellets. By applying this novel technique, fibres with unique adsorbent properties and a high surface area per unit volume ratio can be prepared with a range of adsorbents to target a range of pollutants. The proposed method is not just limited to HiSiv 3000; in principle, many adsorbents or catalysts may be used, which means that this method can pave the way for a new generation of energy-efficient low-pressure-drop adsorbent fibres with low mass transfer resistance.